Identification of Diatoms in Universiti Sains Islam Malaysia Reservoir Ponds, Negeri Sembilan, Malaysia - Adawiyah Nasihah M. Yuni; Athirah Soleha Md Solehhuddin; Izzatul Huda Ahmad Rapee; Mohd Sanusi Mohamed; Mohamad Arif iskandar Abdul Wahab; Mohamad Azani Abd. Khadir Jalani; Ehwan Ngadi (Universiti Sains Islam Malaysia, 2024)
E-Proceeding: Insan Junior Researcher International Conference (iJURECON) 2020 Date: 17-18 November 2020 Organized by: Kolej Genius Insan Virtual Conference Page :38-41